ANALISIS TOKOH DALAM CERPEN TAMU KARYA BUDI DARMA: KAJIAN PSIKOLOGI SASTRA - Hilda Septriani; Erfina Mulyasih (Media Bahasa, Sastra, dan Budaya Wahana, 2022)
Prose literature is a literary work that has fictional characters in it. One of them is a short story Tamu by Budi Darma which has fictional characters with psychological phenomena like humans in general. The psychological phenomena of these characters can be analyzed with a literary psychology approach. Guest short stories by Budi Daram will be the object of this research. The purpose of this study is to describe the psychological phenomenon of Tini's character in the short story Tamu by Budi Darma using a literary psychology approach, especially Sigmund Freud's psychoanalytic theory because this research focuses on the analysis of the id, ego, and superego of Tini's character in Budi Darma's short short story Tamu by Budi Darma. The research method used in this study is a qualitative descriptive research method. The data in this study comes from the short story Tamu Karya Budi Darma, in the form of sentence quotes or dialogues that show the personality structure of Tini's character. Data collection techniques using reading and note-taking techniques. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the structure of the Id and ego is more dominant in controlling Tini in her daily life. However, the superego can limit the ego and id in Tini, making her loosen up her ego and id a little. These three personality elements greatly influence Tini in making decisions and actions.